Developing listening skills among the educable mentally retarded children intermediate level - Acance, Remedios P. 1941- (College of Education, University of the Philippines Diliman, 1972)
The study suggests factors, principles and activities in the development of listening skills among the educable mentally retarded in the intermediate level. Specifically, the study seeks to know the learning characteristics of the educable mentally retarded in the intermediate level, why listening is important to the educable mentally retarded, the factors involved in developing listening skills, the principles that can be successfully utilized by special education teachers in developing listening skills among the mentally retarded in the intermediate level, and the activities designed to broaden and deepen the listening skills among the educable mentally retarded in the intermediate level.